(3QaY GdedGe Yef NaV hGdO TjN GdHNGQi eMeO Hf SdGes - (3TeS GdOjf eMeO Hf YHO Gddg Hf eMeO GdbjSi GdOeTbj GdeYQha HGHf fGUQ GdOjf,J (B842 (3g` s ((3fLe GdOjf YeQ Hf eMeOH agO GdgGTei s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdbOhS GdSdGe CeG HYO abO hbaJ Ydi eUfa dWja Cdag GdSjO GHh Ydi eMeO GdLhjfi SeGg eNJUQkG ef GdcdGe ai GdaQb Hjf ef GSe CHjg SdGe hSdGe s
(3BNQgG (B:s
(3hCeG GdHjcfOi GdUZjQ GdPi JbOe aJhbi ajeG bjd HeUQ hGddg SHMGfg hJYGdi CYde hgPG BNQ eG HQ Gddg JYGdi ef GdcdGe Ydi hGdO TjN GdHNGQi eMeO Hf SdGe BNQ QaY GdedGe Yf ef Naa hGdO TjN GdHNGQi eMeO Hf SdGe s
(3cJHJ HNW eged GdfbW CMjGfkG fbdG Yf fSNI HNW GdeDdas
(3hYdi MGTjI fSNJfG gPg SeGY heYGQVI HNW GdeDda hHBNQgG SeGY SfI (B837 (3Ydi GdeDda ef YOI YdeGA efge GdfGSN faSg hTgO GdeDda Ydi gPG GdSeGY hELGRI HNWg s
(3hUaMg GdYdGa CjVkG HNW GdeDdas
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdeLGejYs